Magnitude and Predictors of Health Care Workers Depression During the COVID-19 Pandemic: Health Facility-Based Study in Eastern Ethiopia - Yadeta, Tesfaye Assebe; Dessie, Yadeta; Balis, Bikila (Frontiers in Psychiatry, 2021)
Abstract Background: Depression of health care workers was related to work absences, resignations, and poor work performance, affecting the quality of patient care and the health care system. It may be at higher risk during the Coronavirus disease (COVID-19) pandemic. There is limited evidence that assesses depression and its associated factors in the study area. Therefore this study aimed to assess depression and associated factors among health care workers (HCW) in eastern Ethiopia. Method: The cross-sectional study design was conducted from October 26th to November 10, 2020. To assess depression among health care workers. Patient Health Questionnaire (PHQ-19) questionnaire was used for the collection of depressive symptoms. The data were analyzed by using STATA version 14 software. Adjusted Odds Ratio (AOR) along with 95% CI was estimated to examine factors associated with depression symptoms using logistic regression analysis. Results: Of the total 265 study participants, 176 (66.4%) and 95% CI: 60.4%, 71.8% of them reported depressive symptoms. Of 176 reported symptoms of depression 27.9%, 24.1%, 9.4%, 3.7%, and 1.1% were had minimal, mild, moderate, moderate-severe, and severe depressive symptoms respectively. Being female [AOR: 3.40, (95%CI: (1.79, 6.45)], participants who perceived susceptibility to COVID-19 [AOR: 2.30, (95%CI: (1.12, 4.71)], and perceived severity to COVID-19 [AOR: 3.06, (95%CI: (1.35, 6.91)] were higher risks of experiencing depression symptoms. Participants who had work experience 3-5 years [AOR: 0.21, (95%CI: (0.08, 0.56)], and the participant who had 6-10 years’ work experience [AOR: 0.30, (95%CI: (0.11, 0. 84)] were had less likely to experience depression symptoms when compared with a participant who had two and fewer years of work experience. Conclusions: A high proportion of health care workers experienced depression symptoms. Health care workers' mental health needs to be protected during the COVID-19 pandemic. Female health care workers, junior health care workers, and HCWs perceived susceptibility, and perceived severity of COVID-19 need attention.